[RETRACTED] IMPROVING ENGLISH LANGUAGE ABILITY OF CHILDREN AGED 4-5 YEARS OLD BY USING CREATIVE DANCE - Sabila Nur Masturah; Myrnawati Myrnawati; Sofia Hartati; Elindra Yetti (OKARA: Jurnal Bahasa dan Sastra, 2018)
Following careful and considered a review of the article entitled “IMPROVING ENGLISH LANGUAGE ABILITY OF CHILDREN AGED 4-5 YEARS OLD BY USING CREATIVE DANCE", Vol. 12, No. 1, Mei 2018 by Sabila Nur Mastura, Myrnawati, Sofia Hartati, and Elindra Yetti. DOI: 10.19105/ojbs.v12i1.1759The article has been found to be in violation of the Publication principles of OKARA: Jurnal Bahasa dan Sastra, the article contains intentional academic misconduct. The editor investigated and found that the article published in JETL (Jurnal of Education Teaching and Learning), Vol. 3, No. 1, 2018, http://journal.stkipsingkawang.ac.id/index.php/JETL/issue/view/79The document and its content have been removed from OKARA: Jurnal Bahasa dan Sastra, and reasonable effort should be made to remove all references to this articles.